MENUMBUHKAN DISIPLIN DIRI MELALUI DISIPLIN POSITIF RESTITUSI - Adlan Surya Saputra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The method of giving punishment in creating self-discipline in students is not effective. The punishment given will stimulate bullying in schools. The impact of punishment not only hurts physically but also mentally. They will grow into someone who is inferior and anti-social. In learning they become passive because they only focus on avoiding punishment. Likewise, giving rewards is not effective in fostering self-discipline in learners. This method actually makes learners dependent on rewards for good behavior and is counter-productive to the goal of self-discipline. Rewards do not foster internal motivation, responsibility and resilience in learners. This research uses the literature review method where data is obtained from various sources such as journals, e-books, and relevant references according to the topic raised. Positive discipline guides learners in fostering internal motivation so as to create long-term self-discipline. Positive discipline gives learners the freedom to correct and learn from their mistakes. Restitution is part of positive discipline with three steps, namely; 1) Stabilizing Identity; 2) Validating wrong actions; 3) Questioning class beliefs. The end result of the application of restitution positive discipline is the birth of self-discipline in students which is characterized by long-term good behavior. Schools that implement restitution positive discipline successfully reduce the number of offenses, learners are more likely to respect school rules and consider the consequences of their actions before violating. This indicates that restitution is successful in reducing negative behavior and bringing about long-term changes in learners' behavior.